Chemotherapy-induced alterations in miRNA expression and their prognostic implications in ovarian cancer - Ranmale, Samruddhi; Kumar, Pavan; Tongaonkar, Hemant; Mehta, Sanket; Maniar, Vashishth; Mania-Pramanik, Jayanti (Frontiers in Oncology, 2025)
IntroductionOvarian cancer has a high mortality rate due to late diagnosis, relapse and chemoresistance. miRNAs play a major role in tumorigenesis as well as chemoresistance. Hence, we undertook a study, to evaluate the differential expression of miRNAs in clinical specimens of ovarian cancer patients that may highlight the effect of chemotherapy and their role in predicting survival outcomes.MethodsClinical specimens were collected from n=127 participants comprising chemo-naive, chemo-treated ovarian cancer patients and healthy women as controls for the study. miRNA expression was evaluated by quantitative real-time PCR analysis.ResultsOur results indicate an upregulation of miR-182 and miR-130a in the serum of treated ovarian cancer patients, which may be an effect of chemotherapy. Tissue levels of miR-182 and miR-106a were elevated in patients with advanced-stage disease. Elevated tissue expression of miR-106a was also associated with poor chemotherapy response and early relapse, while miR-200a was elevated in metastatic patients and linked to early relapse. However, reduced tumor suppressor miR-433 and miR-145 levels were observed in metastatic patients. Multivariate Cox regression identified serum miR-130a and tissue miR-20a as independent predictors of progression-free survival. A combined serum miRNA panel (miR-182, miR-106a, miR-23b) demonstrated diagnostic potential with an AUC of 0.743.ConclusionThe study highlights differential regulation of circulating and tissue miRNAs in Indian OC patients, emphasizing the selective retention of oncogenic miRNAs in tumors and release of tumor suppressive miRNAs into circulation. These findings support the utility of miRNAs as diagnostic and prognostic biomarkers in OC.